Herbal medicines in the treatment of children and adolescents with attention-deficit/hyperactivity disorder (ADHD): An updated systematic review of clinical trials - Haide Golsorkhi; Mostafa Qorbani; Saeideh Sabbaghzadegan; Majid Dadmehr (Mashhad University of Medical Sciences, 2023)
Objective: This study was performed to provide an updated systematic review of herbal medicines and phytochemicals used for treatment of the pediatric patients with attention-deficit/hyperactivity disorder (ADHD).Materials and Methods: International electronic databases, including Scopus, PubMed, ScienceDirect, and Google Scholar were investigated from 1st January 2000 to late October 2021. Interventional studies published in English language, including randomized controlled trials (RCTs) or open-label clinical studies, which evaluated the effect of herbal medicines and phytochemicals on pediatric ADHD were included in this review.Results: Fifteen studies met the inclusion criteria. Several pieces of evidence support the efficacy of Ginkgo biloba L. and Pycnogenol; mainly inconclusive evidence could be found for Valeriana officinalis L., Melissa officinalis L., and ginseng. The results showed that while Hypericum perforatum L. was ineffective for ADHD, Passiflora incarnata L., Crocus sativus L, and Prunus dulcis (Mill.) D.A.Webb had similar efficacy compared to methylphenidate (MPH).Conclusion: A number of herbal medicines appear to be relatively safe and provide potential efficacy in amelioration of ADHD. However, due to lack of adequate reports of RCTs, no definitely specific recommendations could been made so far.